Expressional variations of Kaiso: an association with pathological characteristics and field cancerization of OSCC - Shaheen Ahmed; Saeed Khan; Muhammad Asif Qureshi; Uzma Bukhari; Mehak Anis; Muhammad Nouman Mughal (BMC Cancer, 2022)
Abstract Background A group of genetically altered cells that have not transformed into a clinical or histologically identifiable state of malignancy but contains a higher risk of transforming into one is known as the field of cancerization. Numerous molecules are being investigated for their significance in the development of this phenomenon. One such protein of this family is Kaiso also known as ZBTB33 (Zinc Finger and BTB Domain containing 33). This protein belongs to the POZ-ZF family of transcription factors and may have functional tasks similar to its other siblings such as the growth and development of vertebrates and the pathogenesis of neoplastic diseases. Nevertheless, its role in the pathogenesis, progression, epithelial mesenchyal transition and field cancerization in case of oral cancer still needs exploration. Hence, this study was designed to explore the expressional differences between the mucosa of controls and those diagnosed with oral squamous cell carcinoma (OSCC). Methods Soft tissue samples were obtained from the main tumor, tumor periphery and opposite buccal mucosa of 50 oral cancer patients, whereas normal mucosa was taken from 50 volunteers undergoing elective tooth removal. The acquired samples were subjected to Immunohistochemical exploration for expression of Kaiso and E-Cadherin. The expression was measured using Image-J IHC profiler and summed as Optical density. The Optical density values were then subjected to statistical analysis. Results Results revealed a significant differential expression of Kaiso between the mucosal tissues taken from oral cancer patients and controls (p-value: < 0.0001), showing almost 50% down-regulation of Kaiso in all three tissue samples taken from oral cancer patients as compared to normal mucosa. Conclusion Kaiso has a significant difference of expression in the mucosa of oral cancer patients as compared to the mucosa of normal patients, making it a probable contributor to disease pathogenesis and field cancerization.